Penerapan Modeling Transportasi Sebagai Dasar Penyusunan Rencana Induk Jaringan Jalan - Rahayu Sulistyorini (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
In the development of transportation, government had role as guidance, so they have obligated toprepare and formulated transportation policy, control and monitor implementation of transporta-tion. One obligation referred to is setting transportation infrastructure network and level of ser-vice. Other important thing is performing prediction the movement of passengers and goods espe-cially on each point of transportation movement, related to road network master plan.The main objective of this research is the application of modeling transport in road network plan-ning. Other policies that will follow are the settings and policies regarding to freight circulation interminal, the recommendation of public transport and road network system. Four stages of trans-portation planning is used as a research method.The result of this study is recommendation that necessary to preserve transportation service in ru-ral areas to develop primary transportation based on community and land use development. Rec-ommendation of road network master plan is resettle of road level and function based on activity,new corridor development connecting under development area and nationality conection.